Farm commercialization: A transformation on hold or in reverse? - Minten, Bart; Fang, Peixun; Naing, Phyo Thandar; Aung, Zin Wai; Ei Win, Hnin (International Food Policy Research Institute, 2024)
When food systems transform, farmers’ interactions with markets change dramatically. With changes from traditional to transitional to modern systems—as defined by Reardon and Minten (2021)— farmers move from mostly subsistence-oriented agriculture with few market interactions toward heavy reliance on spot markets for inputs, outputs, and services, and ultimately to contract farming. Such reliance on markets during these transformation processes has been shown to lead to significant improvements in farm performance and in agricultural households’ welfare.